1969
DOI: 10.1017/s0022149x00004806
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Liver, Lung, Brain and Blood of Experimental Animals Infected withToxocara canis

Abstract: Studies were carried out in mice and a monkey (paratenic hosts) and pathological lesions in mice have been described in liver, lung and brain with Toxocara larvae moving actively in the tissues causing damage (haemorrhages and necrosis) with encystment. In both mice and monkey there is essentially an eosinophilic response with lymphocytes and neutrophils also showing rise in the peripheral blood a few days after infection. In mice lymphocytes are the predominant tissue inflammatory cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
4

Year Published

1972
1972
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
2
17
1
4
Order By: Relevance
“…In addition, we frequently observed the simultaneous presence of larvae in liver, lungs, brain, eye, and heart at the same time interval during early reinfection. Since histology showed intra-as well as extravascular locations in biopsies from liver and lungs, our findings indicate that, beside migration via the systemic circulation, the parasites migrated through tissues and the body cavity, as suggested by /1985, Bisseru (1969), and Burren (1968). Pecinali et al (2005) supposed that this situation may occur due to larger fenestrations and/or a discontinuous capillary system in the host organs.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, we frequently observed the simultaneous presence of larvae in liver, lungs, brain, eye, and heart at the same time interval during early reinfection. Since histology showed intra-as well as extravascular locations in biopsies from liver and lungs, our findings indicate that, beside migration via the systemic circulation, the parasites migrated through tissues and the body cavity, as suggested by /1985, Bisseru (1969), and Burren (1968). Pecinali et al (2005) supposed that this situation may occur due to larger fenestrations and/or a discontinuous capillary system in the host organs.…”
Section: Discussionsupporting
confidence: 65%
“…It is difficult to explain how relatively large parasites (size about 400×15-20 μm) can pass through pulmonary capillaries with diameter of which is 8 μm to systemic circulation. The findings of larvae in the brain at the same time interval when the lungs become invaded suggest, however, that the parasites migrated through tissues or body cavity as suggested by Abo-Shehada et al (1984/85), Bisseru (1969) and Burren (1968). Pecinali et al (2005) recorded unexpected presence of T. canis larva in the heart before it reached the lungs and suggested that migratory routes might be explained by the presence of pores (fenestrations) of different size in the vascular endothelium of various organs through which the parasites escape and migrate further; probably larger pores and/or discontinuous capillary system can be associated with an earliest larval development.…”
Section: Discussionmentioning
confidence: 74%
“…The main migratory route taken to and from the liver and lungs to other organs seems to be blood vessels, although histological evidence suggests that migration through tissues and body cavity occurs also (Abo-Shehada et al 1984/85;Bisseru 1969;Burren 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmada, larvaların daha uzun süre bağırsakta kalabildiğini kaydeden çalışmalara benzer şekilde enfeksiyonun 8. gününde kontrol grubunda bağırsakta larvaya rastlanmış, ancak bu günden sonra bağırsakta larva görülmemiştir. Larvaların ikinci günden itibaren karaciğerde, üçüncü günden itibaren ise akciğerde bulunabildiği ve 5. güne kadar karaciğerde, 8.güne kadar ise akciğerde yüksek olan sayının bu günlerden itibaren hızla azaldığı, ancak larva bulunma durumunun devam ettiği bildirilmektedir (6,7,16,18,22 …”
Section: Tartışma Ve Sonuçunclassified